The Influence of Problematic Social Media Use on Impulsive Buying in Early Adulthood in Padang City - Anggi Adhari; Rahayu Hardianti Utami (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
The amount of interesting information on TikTok that TikTok users see will make users interested and often there is a sudden and unconscious desire to buy a product without any prior planning or it is called impulsive buying. This is because many and often individuals access TikTok for a long time or because they are in a negative mood if they do not access TikTok. This research aims to determine the problematic social media use on impulsive buying among early adult TikTok users in the city of Padang. This research design uses quantitative sampling techniques used namely purposive sampling. The sample in this study was 200 respondents whose characteristics were determined by the researcher to be used as samples. The results of the data were processed and analyzed using simple linaer regression analysis techniques, obtaining values of r = 0,535 and p = 0,000. The final results of the research show that there is a positive influence of the independent variable (problematic social media use) on the dependent variable (impulsive buying). These results show that the higher the problematic social media use in early adults using TikTok the higher impulsive buying.